Passive systems for buildings using buoyancy-driven airflows - Abreu, Maria Isabel (2014)
The need for countries to become less dependent on fossil fuels has been a determining factor in recent years due to increasing energy and comfort concerns in modern building design. Therefore, the maximization of the use of renewable energies, like the sun, and the use of natural energy flows become strategies to explore. There are already passive building systems that show interesting performances. Different studies have proved that the above-mentioned systems can lead to important energy savings. However, these systems have their limitations and new innovative building solutions are needed, mainly in the field of passive solar energy collection and natural ventilation strategies. Furthermore, building envelopes face nowadays a new paradigm in which buildings need to be more reactive and adaptive to external climate changes and indoor thermal comfort demands. Hence, this paper makes a review of the most recent patents on building solar air systems that make use of solar energy to induce the buoyancy effect for heating, cooling and ventilating. The patents presented demonstrate the increasing tendency in the development of building passive solutions that can satisfy, in just one system, more than one role: heating, cooling and ventilation.